Study protocol for SFX-01 after subarachnoid haemorrhage (SAS): a multicentre randomised double-blinded, placebo controlled trial - Ardalan H Zolnourian; Stephen Franklin; Diederik Oliver Bulters (BMJ Open)
Introduction Subarachnoid haemorrhage (SAH) from a ruptured cerebral aneurysm carries high morbidity and mortality. Despite huge advances in techniques to secure the aneurysm, there has been little progress in the treatment of the deleterious effects of the haemorrhage.Sulforaphane is an Nrf2 inducer with anti-oxidant and anti-inflammatory properties. It has been shown to improve clinical outcome in experimental models of SAH, but is unstable. SFX-01 (Evgen Pharma) is a novel composition comprised of synthetic sulforaphane stabilised within an α-cyclodextrin complex. On ingestion, the complex releases sulforaphane making SFX-01 an ideal vehicle for delivery of sulforaphane.Methods and analysis The objective of the study is to assess the safety, pharmacokinetics and efficacy of SFX-01. This is a prospective, multicentre, randomised, double-blind placebo-controlled trial in patients aged 18–80 years with aneurysmal subarachnoid haemorrhage in the previous 48 hours. 90 patients will be randomised to receive SFX-01 (300 mg) or placebo two times per day for up to 28 days.Safety will be assessed using blood tests and adverse event reporting.Pharmacokinetics will be assessed based on paired blood and cerebrospinal fluid (CSF) sulforaphane levels on day 7. A subgroup will have hourly samples taken during 6 hours post-dosing on days 1 and 7. Pharmacodynamics will be assessed by haptoglobin and malondialdehyde levels, and maximum flow velocity of middle cerebral artery will be measured by transcranial Doppler ultrasound.Clinical outcomes will be assessed at days 28, 90 and 180 with modified Rankin Scale, Glasgow Outcome Score, SAH Outcome Tool, Short Form-36, Brain Injury Community Rehabilitation Outcome Scales and Check List for Cognitive and Emotional consequences following stroke. MRI at 6 months including quantitative susceptibility mapping and volumetric T1 will measure iron deposition and cortical volume.Safety, CSF sulforaphane concentration and middle cerebral artery flow velocity will be primary outcomes and all others secondary.Ethics and dissemination Ethical approval was obtained from South Central Hampshire A committee. Outcomes of the trial will be submitted for publication in a peer-reviewed journal.Trial registration number NCT02614742.